Wave Reversal Mode: A New Magnetization Reversal Mechanism in Magnetic Nanotubes - Escrig-Murua, J (Elsevier B.V., 2020)
We have investigated the magnetic properties of 14 nm thick and 1 μm long nickel and permalloy nanotubes with external diameters of 40 and 100 nm as a function of the angle θ at which the external magnetic field is applied. Our results show that the coercivity of 40 nm diameter nickel nanotubes follows a non-monotonic behavior from θ = 0° up to θ = 60°, while that corresponding to permalloy displays an increasing monotonic trend at the same angular range. At θ = 90°, both materials evidence a sharp drop of the coercivity to zero, indicating that the reversal mechanism has changed to a pseudo-coherent rotation. On the other hand, nickel and permalloy nanotubes with 100 nm in diameter exhibit a similar angular dependence of the coercivity, reversing their magnetization through the nucleation and propagation of vortex domain walls for angles lower than 75°. For θ = 90°, a novel striking mechanism, the wave reversal mode (W), arises. This phenomenon leads to an unusual S-type shape in the hysteresis curves at those given parameters, which is until now an effect that has not been reported for these nanostructures. © 2019 Elsevier B.V.